Working in the dark: understanding the pre-suicide state of mind - Campbell, Donald (Routledge, 2017)
Introduction -- Attitudes about suicide over the ages -- Suicide and mental illness -- Psychoanalytic interest in suicide -- The core complex -- Suicide fantasies and the pre-suicide state of mind -- How learning from the patient generates theory -- The role of the father in a pre-suicide state -- Pre-suicide states in adolescence -- Implications for the professional -- Self-mutilation -- A patient's account conclusion